2011
DOI: 10.3324/haematol.2011.049007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of FLT3 mutation load in acute promyelocytic leukemia with t(15;17)/PML-RARA

Abstract: The online version of this article has a Supplementary Appendix. BackgroundCombined treatment with all-trans-retinoic acid and chemotherapy is extremely efficient in patients with acute promyelocytic leukemia with t(15;17)/PML-RARA, but up to 15% of patients relapse. Design and MethodsTo further clarify the prognostic impact of parameters such as FLT3 mutations, we comprehensively characterized the relation between genetic features and outcome in 147 patients (aged 19.7-86.3 years) with acute promyelocytic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 36 publications
(45 reference statements)
5
44
1
1
Order By: Relevance
“…In addition, among hematological parameters significant association of FLT3 ITD was confirmed with higher blast count as seen in other studies [15,19,23] as well as with low platelet count which has also been shown by the study of Schnittger et al [41] on APL patients. In relation to AML FAB subtypes, high incidence of FLT3 ITD was noted in AML M6 (50%) followed by M1 (30%), M5b (29%), M3 (25%) while low incidence was noted in M2, M4 and M5a though difference was not significant.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, among hematological parameters significant association of FLT3 ITD was confirmed with higher blast count as seen in other studies [15,19,23] as well as with low platelet count which has also been shown by the study of Schnittger et al [41] on APL patients. In relation to AML FAB subtypes, high incidence of FLT3 ITD was noted in AML M6 (50%) followed by M1 (30%), M5b (29%), M3 (25%) while low incidence was noted in M2, M4 and M5a though difference was not significant.…”
Section: Discussionsupporting
confidence: 68%
“…4,10 However, after adjustment for the associated WBCs by multivariate analysis (WBC Ն 10 000/L being the most consistent indicator of increased relapse risk after ATRA/CT therapy 11 ), the independent prognostic significance of the S-isoform and/or FLT3-ITD ϩ has most often been lost or marginalized. 3,8,10,[12][13][14] Similarly, in some ATRA/CT trials, ACAs at diagnosis were associated with increased relapse risk by univariate but not multivariate analysis. 8,10,15 In protocol C9710, patients analyzed at diagnosis for FLT3 mutations and ACAs, the only association with reduced disease-free survival (DFS) was a complex karyotype (Ն 2 ACAs; X.P.…”
Section: Introductionmentioning
confidence: 96%
“…12 A German study found that patients with FLT3 mutation/wild-type ratio of 0.5 or over had better 2-year OS and EFS rates compared to patients with a ratio less than than 0.5. 13 In the PETHEMA/HOVON experience, 14 in univariate analysis FLT3-ITD mutations were associated to higher relapse and lower OS not retained in multivariate analysis, probably due to a shorter median follow up. A Korean group also showed a higher relapse rate in FLT3-ITD + patients with respect to those FLT3-negative.…”
Section: Letters To the Editormentioning
confidence: 99%